1990
DOI: 10.1080/00913847.1990.11710069
|View full text |Cite
|
Sign up to set email alerts
|

Can Regular Sports Participation Slow the Aging Process? Data on Masters Athletes

Abstract: In brief: Even moderate sports participation is associated with enhanced functional capacity, according to data collected on 554 men and 202 women who underwent maximal exercise testing during the 1985 World Masters Games in Toronto. Their training was modest relative to elite competitors. Nevertheless, their peak power output during cycle ergometry and peak oxygen intake were above the norm for nonathletes of the same age, resembling the values of sedentary 25-year-olds. Such gains have major implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…VO 2max is estimated to decline approximately 10% per decade after the age of 25 years in healthy sedentary aging individuals [15]. An age-related reduction in VO 2max has also been well documented in both cross-sectional and longitudinal studies of male and female endurance athletes undertaking high levels of endurance training into older age [11,32,40,42,48,53,56,57,71,72,78,106,108], suggesting that some decrease in VO 2max appears inevitable with aging, despite physical training into older age. However, the rates of decline in VO 2max have been reported to be reduced [54,55,78], similar [108], or greater [47,71] than age-matched sedentary individuals.…”
Section: Maximal Aerobic Powermentioning
confidence: 99%
See 2 more Smart Citations
“…VO 2max is estimated to decline approximately 10% per decade after the age of 25 years in healthy sedentary aging individuals [15]. An age-related reduction in VO 2max has also been well documented in both cross-sectional and longitudinal studies of male and female endurance athletes undertaking high levels of endurance training into older age [11,32,40,42,48,53,56,57,71,72,78,106,108], suggesting that some decrease in VO 2max appears inevitable with aging, despite physical training into older age. However, the rates of decline in VO 2max have been reported to be reduced [54,55,78], similar [108], or greater [47,71] than age-matched sedentary individuals.…”
Section: Maximal Aerobic Powermentioning
confidence: 99%
“…HR max has been shown to decrease in both males and females [47] at the same rate in both aging athletes and sedentary populations [54,56,57,71,72,108] at approximately one beat per year after the age of 10 years. Hawkins et al [47] examined longitudinal changes in VO 2max , HR max , and training volume in 86 male (53.9± 1.1 year) and 49 female (49.1±1.2 year) masters endurance runners over an 8.5-year period.…”
Section: Central Factors Affecting Maximal Aerobic Powermentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, protein needs for mature adults in RT might be lower than for younger individuals because of the decrease in whole-body protein turnover and protein synthesis with aging (Morais et al, 1997;Nair, 1995) and because older individuals do not train with the same intensity or duration as younger people (Kavanagh & Shephard, 1990;Walter, Hart, Sutton, McIntosh, & Gauld, 1988). For those reasons, Sacheck and Roubenoff (1999) .…”
Section: Protein Needs Of Older Adults Engaged In Resistance Trainingmentioning
confidence: 99%
“…Another senior athlete of that time period is still competing at the age of 80. Data collected at the 1985 World Master's Games in Toronto [2] found that even those older athletes who only participated marginally enjoyed higher levels of overall health and well-being than their more sedentary counterparts. Master Athletes who train vigorously for athletic competitions resemble many younger athletes in terms of such D DAVID PUBLISHING factors as aerobic power, lower blood pressure, and lean body mass [3,4].…”
mentioning
confidence: 99%